Water Supply and Sanitation in Nigeria : Turning Finance into Services for 2015 and Beyond - World Bank (Washington, DC, 2014)
This analysis aims to help Nigeria assess its own service delivery pathways for turning finance into water supply and sanitation services, in the subsectors of rural and urban water supply, rural and urban sanitation, and hygiene. This second Country Status Overview (CSO2) compares Nigeria's own estimates of coverage with data from the UNICEF/WHO Joint Monitoring Programme (JMP). The impact of these different coverage estimates on investment requirements is also assessed. The analysis, commissioned by the African Ministers Council on Water (AMCOW), has three main components: a review of past coverage; a costing model to assess the adequacy of future investments; and a scorecard which allows diagnosis of particular bottlenecks along the service delivery pathway. This Country Status Overview's (CSO2) contribution, is to answer not only whether past trends and future finance are sufficient to meet sector targets, but what specific issues need to be addressed to ensure finance is effectively turned into accelerated coverage in water supply and sanitation. In this spirit, specific priority actions have been identified through consultation.